Cognitive Profiles of Amyotrophic Lateral Sclerosis Differ in Resting-State Functional Connectivity: An fMRI Study - Temp, Anna G. M.; Dyrba, Martin; Büttner, Charlotte; Kasper, Elisabeth; Machts, Judith; Kaufmann, Jörn; Vielhaber, Stefan; Teipel, Stefan; Prudlo, Johannes (Frontiers in Neuroscience, 2021)
Background: Half of all Amyotrophic lateral sclerosis (ALS) patients are classified as ALS-frontotemporal spectrum disorders (ALS-FTSD), of which 10% have frontotemporal dementia (FTD) and additional 40% suffer from a frontotemporal syndrome not severe enough to be described as dementia (cognitively impaired/ALSci). As changes in cerebral function measured by resting-state magnet resonance imaging (rs-fMRI) are known in ALS, we investigated whether group differences in resting-state functional connectivity (RSFC) networks could be observed between ALS patients with different cognitive profiles against healthy controls (HC). Furthermore, we correlated cognition and motor functioning with network connectivity. Methods: 69 healthy controls and 97 ALS patients underwent functional MRI scanning and cognitive assessment. The ALS patients were categorized as non-impaired (ALSni; n=68), cognitively impaired (ALSci; n=21), and ALS-FTD (n=8). Group differences in connectivity of the default mode network (DMN), motor network (MN), and ventral attention network (VAN) were investigated using a full-factorial model; correlations between global cognitive performance, shifting and motor symptom severity were established using Pearson’s correlation. Results: At a very liberal alpha level of uncorrected p<.005 and a cluster size exceeding 20 voxels, we found wide-spread decreases in functional connectivity in all three networks when comparing ALS patients to HC. Similar patterns of hypoconnectivity in the bilateral motor cortices and frontotemporal emerged when comparing the ALSci and ALS-FTD patients to those not cognitively impaired. Simultaneously, ALS-FTD patients showed higher VAN connectivity than ALSni patients in their right putamen. Hyperconnectivity in the DMN temporal gyrus correlated with worse global cognition; moreover, hyperconnectivity in the VAN thalamus, insula and putamen correlated with worse shifting ability. Better-preserved motor function correlated with higher MN connectivity. Only the motor-related effects prevailed at a more conservative significance level of pFDR<.001. Conclusions: Resting-state functional connectivity differs between cognitive profiles of ALS, and is directly associated with clinical presentation, specifically with motor function and cognitive shifting.